Risk Appraisal of Itagunmodi Mining Site for Heavy Metals - Abiodun, Fatoye Olaniyi; O, Adebayo Albert (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 4 No 1&2 (2017): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Heavy metal contamination of agricultural soils and crops surrounding the mining areas is a serious environmental problem in many countries including Nigeria. Mining and smelting operations are important causes of heavy metal contamination in the environment. The pollution characteristics of Cu, Ni, Cd, Cr, Zn and Fe in goldmine tailing were studied. The results indicate that the contamination degree followed the sequence of 5>1>3>2>4. The concentrations of Cu, Zn Ni and Cr in the soil were low, so their potential ecological risks were far lower than other heavy metals and exerted no potential harm to environment.